Maritime common good and coastal zone management - Debelić, Borna (Array, 2018)
This paper aims to develop the concept and the definition of the maritime common good, its sub components and sub layers and to classify and analytically systematize it in the framework of modern theories addressing economic goods. Possible theoretical advancements and extensions in classification criteria are provided. International formal institutional framework is presented and elaborated. The accent is given to the development of theoretical concept and classification of economic goods as well as development of the Institutional Analysis and Development framework – IAD framework that is used to provide analytical understanding of the maritime good classification as well as allocation problems arising. This is performed in the light of ICZM protocol addressing coastal zones as of special concern particularly considering the intensive interrelations between humans and coastal zones. According to the developed classification criteria and analysis performed, the maritime good, as a complex good, can be classified dominantly as common good with limited renewability. The importance of further advancements of maritime common good governing mechanisms based on stakeholders’ inclusion into decision making process is emphasized in order to strengthen the potential of the mechanisms itself and the information background necessary for a successful management of the complex maritime common good.